Políticas do si mesmo : por uma autonomia enquanto função em tempos de biopoder - Gama, Bruno Cerqueira (2010)
This present work, in a political bet for what can escape the present bio-power tricks, is an effort of thinking the theme autonomy , so current in Human Sciences and Psychology discourses. To do this, in a first moment, objectives to formulate, from Michel Foucault s work, the normative operation of the bio-political power technology and how it articulates with games of truth , based on the modern ideal of sovereign rational subject capable to auto-determination. In this case, the possibility of autonomy is understudied as something safeguarded by the possibility of liberation from the environment and social impurities that circulates on the human being. After that, we also discuss the ways how the individual relates to himself, as from a number of historically placed practices, the characther is able to think about himself. This issue that gives us clues to an understanding of this object - the self - as produced in the middle of the contexture of history and not as an essentialized nature belonging to the sovereign individual. Finally, a third thing, it seems that currently, a different autonomy would be bonded directly not to this subject sovereign, but to the life potency to outstrip any normalization and operate as a plane that expands in collectives connections webs; auto-referents webs that continually regenerates, by these interactions and transformations. By this way, it s about thinking autonomy as a collective function bonded, above all, to the invention of singular becoming process, not referent to an individual interiority, natural and intimist, but the production of collectives, these ones not identified to the social , but to a heterogeneous co-engendered plane for both, individual and society. Such bet, in these individual and collective statute acts as an incentive to the political reflection and to the fight for the enhancement of problematic landscapes that own distinctness when what in debate is fundamentally our relation with the present and our compromise to make it less unbearable and more promising.